Credit and Debt Repayment “Need to Knows” for Military Families - Barbara O'Neill; Martie Gillen; Kristen Jowers (EDIS)
This publication is the third in the series on military family readiness. The publication discusses general information about credit and debt repayment, general information about credit reports and scores, military-specific credit-related challenges, military-specific credit-related laws and support services, five credit management tips for military families, and credit education resources. Written by Barbara O’Neill, Martie Gillen, and Kristen Jowers, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2024.